2006
DOI: 10.1177/1352458505070660
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in a population-based sample of people with multiple sclerosis in Stockholm County

Abstract: The aim of this descriptive, cross-sectional study was to analyse health-related quality of life (HRQoL) in a population-based sample of people with multiple sclerosis (PwMS) in Stockholm County, with respect to disease-related and sociodemographic factors and coping capacity. A further aim was to compare our results on HRQoL--collected by face-to-face interviews at home-visits--with the results from a study with a mail-surveyed sample of PwMS in Stockholm. Home visits were made to 166 PwMS with clinically def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
56
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 29 publications
19
56
0
1
Order By: Relevance
“…Chronic and progressive diseases like MS seem to particularly modify an individual's QoL. This is confirmed by studies conducted in Sweden, Germany, Spain, the United States and Canada [13][14][15][16][17]. However, because of cultural and social differences and the organization of the health care system, the results of these studies cannot be directly linked to MS patients in Poland [18].…”
Section: Introductionsupporting
confidence: 61%
“…Chronic and progressive diseases like MS seem to particularly modify an individual's QoL. This is confirmed by studies conducted in Sweden, Germany, Spain, the United States and Canada [13][14][15][16][17]. However, because of cultural and social differences and the organization of the health care system, the results of these studies cannot be directly linked to MS patients in Poland [18].…”
Section: Introductionsupporting
confidence: 61%
“…15,21,[32][33][34][35][36] In one study employing both the SIP and the SF-36, the SIP was shown to have stronger associations with the Multiple Sclerosis Functional Composite (MSFC) and EDSS than the SF-36. 34 Using the SIP, our objective was to determine the relative influence of physical disability and cognitive impairment in predicting HRQOL in a large sample of MS patients.…”
mentioning
confidence: 99%
“…[6][7][8][9] So far, however, there has been no report of any long-term longitudinal study in the UK, although two British population surveys described follow-up of 1 year. 1,10 A recent study from Sweden reported a deterioration over 4 years in HRQoL of women of all ages, and in younger men.…”
Section: Introductionmentioning
confidence: 99%